Immune activation by life-shortening Wolbachia and reduced filarial competence in mosquitoes. - Kambris, Z; Cook, P; Phuc, H; Sinkins, S (2009)
Wolbachia strain wMelPop reduces the longevity of its Drosophila melanogaster host and, when introduced into the mosquito Aedes aegypti, halves its life span. We show that wMelPop induces up-regulation of the mosquito's innate immune system and that its presence inhibits the development of filarial nematodes in the mosquito. These data suggest that wMelPop could be used in the global effort to eliminate lymphatic filariasis and possibly for the control of other mosquito-borne parasites where immune preactivation inhibits their development. The cost of constitutive immune up-regulation may contribute to the life-shortening phenotype.